An Embedded Model of Cultural Adaptation in Global Teams - Cramton, Catherine Durnell; Hinds, Pamela J. (Organization Science, 2014)
This research examines the process through which globally distributed work teams attempt to adapt to cross-cultural differences while being constrained by the local contexts in which they are embedded. We conducted an in-depth field study of nine software development teams that included 132 ethnographic initial interviews, periods of team observation, 19 follow-up interviews, and team meetings. Inductive analysis of the data led us to develop an embedded model of cultural adaptation in global teams to describe the process we observed as teams attempted to cope with important differences in interpersonal communication styles, preferred approaches to organizational control and authority relations, and work-related knowledge and problem-solving approaches. We show how local embeddedness and interdependence across sites together drive cultural adaptation dialectics as actors attempt to resolve rippling tensions within and across nested social structures. The model of cultural adaptation that we developed as an outcome of our research challenges literature that assumes adaptation can be contained within a team and is distinctive in incorporating a dynamic systems view of culture. We build on and develop theory concerning multilevel structuration dynamics. Our work may have implications for other types of boundary-spanning collaborations such as strategic alliances and multinational corporations.